Zhodnocení hospodaření neziskové organizace - Kománková, Marie (Vysoké učení technické v Brně. Fakulta podnikatelská, 2012)
Bakalářská práce se zabývá zhodnocením hospodaření neziskové organizace, konkrétně zhodnocením hospodaření Českého zahrádkářského svazu, ZO Nivnice. V první části bakalářské práce jsou uvedena teoretická východiska. V části druhé je analýza příjmů a výdajů Českého zahrádkářského svazu, ZO Nivnice a část třetí uvádí návrhy na zlepšení hospodářské situace. Cílem práce je zhodnocení jednotlivých příjmů a výdajů a následné doporučení zlepšující finanční situaci organizace.

The goal of this thesis is to evaluate the economy of a non-profit organisation, specifically the economy of the Czech Gardening Organization, ZO Nivnice. The first part concerns the theoretical solutions. The second part is devoted to the analysis of the income and the expense of the Czech Gardening Organization, ZO Nivnice and the third part deals with the possible suggestions for an improvement of its economical situation. The aim of the thesis is the evaluation of the particular incomes and expenses followed by recommendation for the improvement of the financial situation of the organisation.
Evaluation of the Finance Situation of the Non-Profit Organization
Keywords: Nezisková organizace – občanské sdružení – Český zahrádkářský svaz; ZO Nivnice – příjmy – výdaje; Non-profit organisation – civic association – the Czech Gardening Organization; ZO Nivnice – incomes – expenses